Scoping review protocol: The chrononutrition factors in association with glycemic outcomes in adult population. - Guey Yong Chong; Satvinder Kaur; Ruzita Abd Talib; See Ling Loy; Hui Yin Tan; Kok Hoe Wilfred Mok; Ling-Wei Chen; Woan Yie Siah; Yin Yin Chee; Ee Mun June Lem; Hui Chin Koo (PLoS ONE)
Chrononutrition, which examines the relationship between circadian rhythms and nutrition, has been associated with glycemic outcomes in adults. However, published data on delayed meal timing, increased meal frequency and frequent breakfast skipping have shown inconsistent glycemic outcomes due to variations in methodologies and populations studied. This review presents the scoping review protocol designed to map the evidence on the association between chrononutrition factors and glycemic outcomes in adults. The methodology framework from Arksey and O'Malley will be adapted for this scoping review. Relevant publications will be searched on databases including PubMed, EBSCO Host, ProQuest Central, MEDLINE & Ovid, Scopus and Web of Science. This review focuses on original articles published from January 2014 to 2024, involving participants aged 18 years and older, published in English, and encompassing experimental and observational studies. A comprehensive keyword search strategy will be developed to identify relevant articles. Two reviewers will independently screen the abstracts and titles to determine the eligibility. Subsequently, the full text of potentially eligible articles will be reviewed by additional independent reviewer for final inclusion, with full text screening being verified by two reviewers, and interrater reliability will be conducted. Data from the included articles will be extracted, collated and charted to summarize the relevant methods, outcomes and key findings. This Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist will be used to guide the development of protocol. This scoping review represents a novel approach to summarize the association between chrononutrition factors and glycemic outcomes among adults. We anticipate the findings of the review will provide stakeholder with crucial evidence-based information for development of effective intervention to manage glycemic outcome in adults. This protocol has been prospectively registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/PA9BU).